Clays and Clay Minerals, Vol. 57, No. 2, 251–263, 2009. - Sengupta, Aniruddha (My University, 2009)
The potential for structural failure of consolidated clay materials, which is of great importance in many applications, typically are assessed by measuring the localized strain bands that develop under anisotropic load stress. Most methods are precluded from providing a full understanding of the strain anisotropy because they only give two-dimensional information about the stressed clay blocks. The purpose ofthe present study was to investigate three-dimensional strain localization in a kaolinite matrix, caused by strain anisotropy due to a biaxial plane-strain test, using a relatively new method known as Anisotropy of Magnetic Susceptibility (AMS). This method involves induction of magnetism in an oriented sample in different directions and measurement of the induced magnetization in each direction. The AMS analyses were performed on core samples from different parts of the deformed kaolinite matrix. The degree ofm agnetic anisotropy (P’), which is a measure ofthe intensity of magnetic fabric and a gauge ofs train intensity, was shown to be greater in cores containing shear bands than in those containing none. A threshold value for P’ for the deformed kaolinite matrix was identified, above which shear bands may develop. The comparison of the shape parameter (T), obtained from undeformed and deformed samples, illustrated a superimposition ofprolat e strain over the original oblate fabric ofthe kaolinite matrix. The orientation ofthe principal strain axis revealed that reorientation or rotation oft he principal axis occurred along the shear bands.
Anisotropy Of Magnetic Susceptibility Study Of Kaolinite Matrix Subjected To Biaxial Tests
gsccm57211-sen.pdf: 765KB
Keywords: Periodicals; Geology; Anisotropy of Magnetic Susceptibility; Biaxial Test; Kaolinite; Strain Localization